2013
DOI: 10.1097/mpg.0b013e3182a6993d
|View full text |Cite
|
Sign up to set email alerts
|

Mexican American Children Have Differential Elevation of Metabolic Biomarkers Proportional to Obesity Status

Abstract: We observed that Mexican American children as a function of body weight had elevated serum concentrations of several biomarkers that have been linked to chronic disease development in adults. More research is needed to understand how these differences affect disease risk in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
7
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
6
7
0
1
Order By: Relevance
“…In the case of the present study, reduced IL-12p70 with probiotic supplementation may reflect a reduction in systemic inflammatory capacity. In addition to the biomarkers that reached significance, we also found similar numerical trends for IL-6, IL-8, and MCP-1, which are all released by adipose tissues and commonly elevated in obese individuals[ 27 , 31 , 39 ]. The biomarkers observed to change in the present study following the probiotic intervention are involved in the accumulation of systemic inflammation[ 38 , 40 - 43 ].…”
Section: Discussionsupporting
confidence: 53%
“…In the case of the present study, reduced IL-12p70 with probiotic supplementation may reflect a reduction in systemic inflammatory capacity. In addition to the biomarkers that reached significance, we also found similar numerical trends for IL-6, IL-8, and MCP-1, which are all released by adipose tissues and commonly elevated in obese individuals[ 27 , 31 , 39 ]. The biomarkers observed to change in the present study following the probiotic intervention are involved in the accumulation of systemic inflammation[ 38 , 40 - 43 ].…”
Section: Discussionsupporting
confidence: 53%
“…Previously reported associations between metabolic and inflammatory biomarkers and body composition variables (Eriksson et al, 2010;Larsson et al, 2011;McFarlin et al, 2013;Pedrosa et al, 2011;Roth & Reinehr, 2010) were confirmed also in this study cohort, with the exception of the reported inverse association between total adiponectin and indices of body composition and anthropometrics (Eriksson et al, 2010;Pedrosa et al, 2011). We analysed the HMW isoform of adiponectin, which is reported to be more strongly associated with insulin resistance and the metabolic syndrome than total adiponectin concentrations (Hirose et al, 2010).…”
Section: Discussionsupporting
confidence: 50%
“…Elevated insulin and C-peptide levels are connected to diabetes risk as they indicate metabolic disturbances of glucose sensitivity (McFarlin et al, 2013). In our study population, metabolic biomarker response patterns were identified, where C-peptide was normal in overweight children but elevated in the obese while leptin was elevated in overweight children and then further elevated in the obese.…”
Section: Discussionmentioning
confidence: 88%
“…Studies have analyzed the relationship between these hormones or cytokines and metabolic risk factors according to children's weight status [ 7 , 9 , 10 ]. But few studies have reported the concomitant variations of these factors after a lifestyle intervention [ 7 , 11 13 ].…”
Section: Introductionmentioning
confidence: 99%